Kenya's answer to the Mau Mau challenge - Alport, C. J. M. (International Library of African Music, 1954)
An extract from a lecture - If you are prepared to accept my premise that Mau Mau is African, that these problems are essentially part of the African scene, that we will meet them from time to time elsewhere, and that in order to understand them one has to understand Africa—it will surely follow that in order to combat them one must do so on lines which will have their influence and effect upon the African’s mind. I do not for one moment say that the potentialities of the African mind are different from the potentialities of the European mind. I simply do not know. Scientists assure us that there is no difference, and I am prepared to accept that, but I would emphasise to you that with the different traditions behind the African, we must not expect their reactions to European ideas and standards to be precisely the same as would be expected, and normally would be forthcoming, from Europeans themselves.
Keywords: Race relations; History; Ethnomusicology; Colonies; Colonisation; Mau Mau Rebellion; Kenya; Mau Mau; Great Britain; African Music